Improving Descriptive Text Writing Achievement by Using POWER Strategy - Diah Dwihning Saraswati; Muhammad Yunus; Fiftinova Fiftinova (Faculty of Teacher Training and Education, Universitas Sriwijaya, 2018)
Abstract: The objectives of this study were (1) to find out whether or not there was a significant improvement in descriptive writing achievement before and after the students were taught by using POWER Strategy, (2) to find out whether there was a significant difference in descriptive writing achievement between the students who were taught by using POWER Strategy and those who were not, and (3) to describe the students' ability in writing descriptive text before and after the treatment. The population of this study comprised 349 tenth graders of SMK Negeri 7 Palembang. By using convenience sampling method, sixty-two students were chosen as the sample of this study. The data were analyzed by using paired sample and independent sample t-test SPSS Version 22. The result of paired sample t-test showed that the p-value was lower than the significance level (0.00<0.05). It means that there was a significant improvement in students’ descriptive writing achievement before and after they were taught by using POWER Strategy. The result of independent sample t-test showed that the p-value was lower than significance level (0.00<0.05). It means that there was a significant difference in descriptive writing achievement between the students who were taught by using POWER Strategy and those who were not. The result of the students' text analysis showed that the students' performance before the treatment was still low as they still confused in identifying the schematic structure of descriptive text. Moreover, they seemed to have less sense of English grammar as they still made a lot of mistakes in the text they wrote. Meanwhile, the students' performance after the treatment was better. They had a good control of the schematic structure and linguistic features of descriptive text.Keywords: Improvement, Descriptive Text, POWER Strategy